SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL STUDIES OF Cu (II), and Ni (II) COMPLEXES DERIVED FROM 2-HYDROXYBENZALDEHYDE AND 2 AMINOPYRIDINE - Sani, Ibrahim; Hussaini, Sunusi Y.; Kutama, Ibrahim U. (FUDMA JOURNAL OF SCIENCES, 2023)
Schiff base ligand derived from condensation of 2-hydroxybenzaldehyde and 2-aminopyridine have been prepared and used to synthesized Cu (II) and Ni (II) complexes, characterized by spectroscopic method (IR spectra). Conductivity, solubility test were determined. On the basis of the infrared studies, appearing of new band around 721 -762 cm-1 and 553- 443 indicate formation of v ( M- N ) and v (M –O ) confirming a coordination of ligand to the metal ion through oxygen and nitrogen atoms. The antimicrobial activities of the complexes was studied against the Staphylococcus aureus, Escherichia coli, Candida albican. The cupper complex showed higher activity than the Nickel complex and the ligand.